2011
DOI: 10.1108/10569211111111676
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Theory of Planned Behavior (TPB) in halal food purchasing

Abstract: PurposeIn this study, Ajzen's Theory of Planned Behavior is used as a theoretical framework with the aim of extending prior research examining halal food purchasing behavior in Malaysia.Design/methodology/approachData are collected through self‐administered questionnaires. This paper uses multiple regression analysis to identify the factors affecting halal food purchasing behavior of Malaysian consumers.FindingsThe multiple regression analysis results indicate that all factors have positive and significant inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
283
5
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(337 citation statements)
references
References 33 publications
36
283
5
13
Order By: Relevance
“…Other researches include Potluri, Rajasekhara Mouly Ansari, Rizwana Khan, Saqib Rasool Dasaraju, Srinivasa Rao [33] who studied Indian Muslims' attitude and consciousness towards halal, Syed Shah Alam Nazura Mohamed Sayuti [23] who examined Applying the Theory of Planned Behavior (TPB) in halal food purchasing. From many research results that mention the importance of halal certification for Muslims, it is expected the food producers begin to consider to register their products to obtain halal label so as to provide a sense of security and confidence to muslim consumers.…”
Section: B Discussionmentioning
confidence: 99%
“…Other researches include Potluri, Rajasekhara Mouly Ansari, Rizwana Khan, Saqib Rasool Dasaraju, Srinivasa Rao [33] who studied Indian Muslims' attitude and consciousness towards halal, Syed Shah Alam Nazura Mohamed Sayuti [23] who examined Applying the Theory of Planned Behavior (TPB) in halal food purchasing. From many research results that mention the importance of halal certification for Muslims, it is expected the food producers begin to consider to register their products to obtain halal label so as to provide a sense of security and confidence to muslim consumers.…”
Section: B Discussionmentioning
confidence: 99%
“…However, the relationship between intention and behavior is built on the assumption that human beings attempt to make rational decisions based on the information available to them [42]. Therefore, behavior that is not consciously performed cannot be explained by the TPB [43]. …”
Section: Theoretical Lensmentioning
confidence: 99%
“…A study by Alam and Sayuti (2011) found that PBC influences the intention to purchase halal food. Martin, Ramamonjiarivelo and Martin (2011) found that PBC is an important factor that influences travel intention.…”
Section: Perceived Behavioural Controlmentioning
confidence: 99%